¿HÉROES O VILLANOS?: LOS ACUERDOS DE COLABORACIÓN EMPRESARIAL Y SU INCIDENCIA SOBRE LA LIBRE COMPETENCIA - Sotomayor Flores, Miguel Eduardo (Revista de Derecho, 2019)
The vertiginous changes taking place in the industry, alongside the appearance of a much more demanding consumer, had created the necessity for corporations to establish alliances in order to overcome their lack on technical, financial, organizational or structural capabilities. Most of the times, these alliances include an agreement or clause that could be deemed to be anticompetitive or signaled as a per se prohibition. Nevertheless, time has proved that these agreements are usually harmless and even able to be procompetitive, forcing competition agencies to be more flexible in their analysis, avoiding ideological bias, thus promoting positive collaborations for the market. In this article, we describe collusive behavior, specifically on technological and retail markets, that is efficient and has positive consequences on the welfare of consumers. We intend to understand the economic reasons behind and study the foreign jurisprudence that addresses them. That on mind, we conclude that we should not only allow these type of alliances, but encourage them through the government.